Puesta en Valor de los pases de niños tradicionales de la zona urbana del cantón riobamba para la conservación del patrimonio cultural inmaterial. - Tene Duchi, Asencio Luis (2016)
The enhancement of intangible cultural heritage is a development tool, responsible for generating social, cultural and economic benefits of a current manifestation, in order to preserve an expression in the present and ensure its sustainability in the future, generating social processes - economic and fulfilling the long-awaited beginning of Good Living. The valorization of traditional Children Passes management has three phases, the first; is the anthropological research phase in which each of the tangible and intangible cultural elements that has the manifestation is recorded, the history and origin, traditions present and cultural elements, the second phase is the analysis of the current situation, was performed by situational and ethnographic, formal diagnosis is finally phase is the plan development dedirectrices safeguarding intangible cultural heritage which was developed based on the methodological guide NCPI. For this research the descriptive scientific method was applied, based on the documentation field the same as was done through consultation of primary and secondary sources, information was also collected in situ through interviews, observations depth and survey the same as those applied to those who participated in the organization, memory carriers and cultural actors.